First model of dimeric LRRK2: the challenge of unrevealing the structure of a multidomain Parkinson's-associated protein - Guaitoli, Giambattista; Gilsbach, Bernd K.; Raimondi, Francesco; Gloeckner, Christian Johannes (Biochemical Society transactions, 2016)
Mutations within the leucine-rich repeat kinase 2 (LRRK2) gene represent the most common cause of Mendelian forms of Parkinson's disease, among autosomal dominant cases. Its gene product, LRRK2, is a large multidomain protein that belongs to the Roco protein family exhibiting GTPase and kinase activity, with the latter activity increased by pathogenic mutations. To allow rational drug design against LRRK2 and to understand the cross-regulation of the G- and the kinase domain at a molecular level, it is key to solve the three-dimensional structure of the protein. We review here our recent successful approach to build the first structural model of dimeric LRRK2 by an integrative modeling approach.